2017
DOI: 10.3832/ifor2123-009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dust exposure during chainsaw forest operations

Abstract: , and in only two samples (one in conifer pruning and one in clear cut in coppice), the concentration was slightly higher than 5 mg m -3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Air sampling results showed that fire fighters exposures to wood dust were above the NIOSH and ACGIH recommended OEL of 1.0 mg/m 3 . These exposures were similar to those measured in forestry workers in central Italy using chain saws [Marchi et al 2017]. During our site visit, fire fighters were primarily cutting small oak trees; however, the kinds of trees or bushes fire fighters cut during fuel reduction can vary by location.…”
Section: Wood Dustsupporting
confidence: 78%
“…Air sampling results showed that fire fighters exposures to wood dust were above the NIOSH and ACGIH recommended OEL of 1.0 mg/m 3 . These exposures were similar to those measured in forestry workers in central Italy using chain saws [Marchi et al 2017]. During our site visit, fire fighters were primarily cutting small oak trees; however, the kinds of trees or bushes fire fighters cut during fuel reduction can vary by location.…”
Section: Wood Dustsupporting
confidence: 78%
“…Few studies have examined exposure of forest operators to wood dust, but it was determined that exposure to dust was 1.5 mg/m 3 for all operations except coppicing, where loads were greater [18]. Most loads, however, were lower than the EU occupational exposure limit (OEL) of 5 mg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that in 25 member states of the European Union, 2% of the work force is occupationally exposed to inhalable wood dust [22]. In the European Union the Directive 99/38/EC [18], is setting the…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor-manual tree felling, processing, and pruning by chainsaws, powered by internal combustion engines, are still very common in many countries [1][2][3][4][5] due to its multifunctional use and low financial investment [6][7][8]. However, the use of chainsaws results in the exposure of workers to hazards such as noise, hand-arm vibrations (HAVs), exhaust gases, and wood dust [9,10]. Chainsaw use shows one of the highest accident rates in professional and non-professional work [11][12][13][14] and causes several types of occupational diseases due to the repeated or continuous exposure to unfavourable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%